Self-Regulation as a Mediator Between Learning Motivation and Academic Procrastination in Students Who Are Preparing a Thesis - Aulia, Aulia; Septiantika, Dewi Fortuna; Perdana, Daviddefikry Yondra; Azis, Agung Putra; Irawan, Dwi Bagus; Fajar, Masyhuril (Universitas Muhammadiyah Yogyakarta, 2024)
Academic procrastination is the failure to complete an academic task within the desired timeframe or postpone the task until the last moment. Academic procrastination can be reduced if students have good self-regulation and motivation. This study aims to empirically test the role of learning motivation in academic procrastination with self-regulation as a mediator. This study uses a quantitative approach with a cross-sectional study. The population in this study is students who are working on a thesis, have worked on at least one semester, and are active in organizations. Sampling was done using purposive sampling techniques. The instruments used are the learning motivation scale, the academic procrastination scale, and the self-regulation scale. The data analysis in this study uses a path analysis technique with the partial least square structural equation model (PLS-SEM). The program or software used to conduct the analysis is SmartPLS 4. The results showed that self-regulation played a mediator between learning motivation and academic procrastination, with a significance value of 0.001 (p<0.05). Coefficient Test -0.242 (p-Value,0.001<0.05). Regulation partially mediates the relationship between learning motivation and academic procrastination. The conclusion of this study states that self-regulation plays an important role in mediating the relationship between learning motivation and academic procrastination in students. In other words, the ability to self-regulate effectively can help students overcome the tendency to delay completing academic assignments.